Speaking truth to power? Anti-bureaucratic romanticism from critical organizational theorizing to the White House - Lopdrup-Hjorth, Thomas; du Gay, Paul (Organization (London, England), 2020)
In spite of their distinctive normative and political differences, critical organizational scholars use a vocabulary which in several respects resembles that adopted by right-wing populists. This vocabulary, we argue, consists of components that can be deployed in the pursuit of radically conflicting goals. At its heart lies a profoundly antithetical stance toward bureaucracy and the state. In this article, we explore the components of this vocabulary as well as the role they play in both populist- and critical organizational theory-variants. In doing so, we further discuss the lack of critical potential this vocabulary has in the present. For critical organization scholars, we argue, this should perhaps lead to a renewed consideration and reflexivity concerning not only the merits of bureaucracy and the state, but also of how to conduct critique in populist times.